2004
DOI: 10.1007/s10820-005-0884-3
|View full text |Cite
|
Sign up to set email alerts
|

On the reconstruction of polycrystalline microstructures from two-point correlation statistics

Abstract: An exhaustive branching technique is introduced for reconstructing discrete microstructures from twopoint statistic occurrences. It is shown that two-point statistics control microstructure, to the extent that exact replicas of discrete microstructures are produced when sufficient two-point statistic occurrences are matched. Efficiency comparisons between simulated-annealing methods and the exhaustive branching method are made on polycrystalline structures and some discussion on advancing the exhaustive branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It has also been shown that the structural ambiguity is considerably larger for a radial function without angular information, which is the only data available from small-angle scattering experiments. However, if angular information is employed successful microstructure reconstructions can often be obtained [18][19][20][21].…”
Section: S T R I B Umentioning
confidence: 99%
“…It has also been shown that the structural ambiguity is considerably larger for a radial function without angular information, which is the only data available from small-angle scattering experiments. However, if angular information is employed successful microstructure reconstructions can often be obtained [18][19][20][21].…”
Section: S T R I B Umentioning
confidence: 99%
“…The DDF, calculated using the morphological parameters, is comprised of N × N number of grain pairs. Each pair contributes a D m i j to DDF according to Equation (17), and each D m is logistically distributed. It is concluded that since DDF for the entire sample shows a good match with the exact DDF, the functional form proposed for D m i j (Equation (16)) is both robust and is statistically representative.…”
Section: Distance-disorientation Functionmentioning
confidence: 99%
“…Considerable research was performed in the field of application of n-point correlation statistics to the problems of three-phase microstructure reconstructions [3,[11][12][13][14][15][16][17][18]. The main idea is to reconstruct the full microstructure media from the n-point correlation statistics using different optimization and homogenization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread use of correlation functions, the nature of the structural information they contain remains an open area of active research [20][21][22][23][24][25][26][27][28]. The central question of the present paper can be put as follows: how accurately is a microstructure known when the only data available is a two-point correlation function?…”
Section: Introductionmentioning
confidence: 99%
“…In the field of computer vision, it has been shown that finite textures are completely characterized by their orientation-dependent correlation functions [33]. Many theoretical examples of microstructures with a low degeneracy can be accurately reconstructed from their correlation function alone [24,25,34,35]. All these examples have in common that they incorporate orientation information [36].…”
Section: Introductionmentioning
confidence: 99%